A practice for specifying user stories in multimedia system design: An approach to reduce ambiguity (2024)
Various agile approaches have guided the development of solutions based on a minimum viable product for the use of user stories (USs). These approaches provide a generic process for specifying USs for a wide variety of solutions. This study presen s an original proposal for a practical approach to the specification of USs for multimedia systems, expressed using the Essence graphical notation language. The practice includes a set of activities, techniques, and tools that can be used by professionals to define the USs of a multimedia system, and which can help to mitigate potential ambiguity problems such as vagueness and insufficiency in formulation. To explore its application, a case study was carried out with the participation of two groups of professionals: an experimental group, and a control group. The results for the analysis factors are promising, and show that by carrying out the activities that make up the practice, a work team can achieve the specification of USs at three levels of concreteness, which contribute to the reduction of problems of vagueness and insufficiency in the USs of a multimedia system. Using this approach, the USs can be guaranteed to meet the value proposition of the multimedia system that will be implemented